A Comprehensive Study on the Microstructure and Mechanical Behavior of Glycoluril–Formaldehyde Polymer-Modified Cement Paste - Nakarajan Arunachelam; S. K. M. Pothinathan; C. Chella Gifta; N. P. Vignesh (Buildings)
Concrete is popular in construction due to its strong performance and low maintenance. However, some structures become unsafe over time due to poor maintenance and design flaws. As demand for maintenance grows, restoring older structures is a cost-effective option. Advanced repair techniques aim to extend service life and improve concrete properties, with a focus on eco-friendly solutions. Recent trends have highlighted the potential of incorporating polymers into repair methods, but the use of glycoluril–formaldehyde, a polymeric material known for its hydrogen bonding capacity, remains unexplored in repairing existing structures. This research investigates the effects of glycoluril–formaldehyde in simple matrices like cement paste and mortar to understand its impact. By examining the chemical reactions between glycoluril–formaldehyde with cement paste, this study delves into the fresh, mechanical, and microstructural characteristics. To evaluate the influence of glycoluril–formaldehyde, cement paste specimens were subjected to various tests, including consistency, initial and final setting time, and miniature slump flow tests. Cement mortar specimens were then subjected to compression strength tests conducted at various ages. The results demonstrate that a 3% addition of glycoluril–formaldehyde in concrete offers optimum performance, ensuring improved mechanical strength and microstructure. The microstructural investigation using optical microscopy, an X-ray diffraction, and SEM analysis confirms the polymerization of glycoluril–formaldehyde and the formation of a denser microstructure. The thermogravimetric (TG) and differential thermogravimetric (DTG) analysis provides crucial insights into the thermal stability of the cementitious system, aiding its characterization for high-temperature applications.